Designing A User-Centred Model to Amplify Satisfaction in Utilizing Online Government Information - Sroukh Alderei, Hamdan Hmoud; Sidek, Safiah (International Journal of Sustainable Construction Engineering and Technology, 2023)
With the increasing reliance on digital platforms for accessing government services and information, user satisfaction becomes a crucial factor in ensuring effective service delivery and citizen engagement. Thus, this study explores into the development of a user-centred model aimed at enhancing user satisfaction in the utilization of online government information. The proposed model integrates Privacy; Safety; Service quality; Time; and Awareness with Satisfaction to create a model that aligns with citizens' needs and preferences. The data collection process targeted respondents among citizens of the United Arab Emirates (UAE) for the questionnaire survey. The respondents were selected using a convenience sampling technique, allowing for the collection of samples conveniently located around a specific area or accessible through internet services. A total of 396 participants took part in the survey and the collected data was used to develop the model using SmartPLS software. The developed model was analysed and the results reveal that the path from Privacy to Satisfaction holds significant influence, as indicated by a T statistic of 3.755 and a p-value of 0.000. Similarly, the paths from Safety and Service Quality to Satisfaction are also significant, with T statistics of 2.363 and 4.580, respectively, and corresponding p-values of 0.009 and 0.000. However, the paths from Awareness and Time to Satisfaction are found to be not significant, with T statistics of 1.162 and 0.935, and p-values of 0.123 and 0.175, respectively. By prioritizing user satisfaction, this research contributes to the advancement of digital government initiatives and citizen-centric service delivery paradigms.